2017
DOI: 10.1016/j.heares.2016.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime leisure music exposure associated with increased frequency of tinnitus

Abstract: Tinnitus has been linked to noise exposure, a common form of which is listening to music as a leisure activity. The relationship between tinnitus and type and duration of music exposure is not well understood. We conducted an internet-based population study that asked participants questions about lifetime music exposure and hearing, and included a hearing test involving speech intelligibility in noise, the High Frequency Digit Triplets Test. 4950 people aged 17–75 years completed all questions and the hearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 27 publications
6
33
0
Order By: Relevance
“…A few other current results are interesting. First, the current prevalence of tinnitus in college students and adolescents was 40%, much higher than past reports (Davis and El Refaie, 2000; 4 Muhr and Rosenhall, 2010; 14 Moore et al, 2016 13 ) but similar to recent reports (Bhatt, 2017; 2 Hinalaf et al, 2017 7 ) where 64% and 59.3% of college students reported occurrence of tinnitus, respectively. Overall, although the current results and these past studies did not all have the same design, the reported tinnitus prevalence of 40-64% indicates that many younger adults and adolescents appear to be susceptible to tinnitus than previously believed.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A few other current results are interesting. First, the current prevalence of tinnitus in college students and adolescents was 40%, much higher than past reports (Davis and El Refaie, 2000; 4 Muhr and Rosenhall, 2010; 14 Moore et al, 2016 13 ) but similar to recent reports (Bhatt, 2017; 2 Hinalaf et al, 2017 7 ) where 64% and 59.3% of college students reported occurrence of tinnitus, respectively. Overall, although the current results and these past studies did not all have the same design, the reported tinnitus prevalence of 40-64% indicates that many younger adults and adolescents appear to be susceptible to tinnitus than previously believed.…”
Section: Discussionsupporting
confidence: 74%
“…Several other variables, including age, gender, socioeconomic status, occupation, smoking, and alcohol, are related to the prevalence of tinnitus (Davis and El Refaie, 2000 4 ). In addition, other factors, including excessive noise, have been studied thoroughly and are well known to be associated with tinnitus (Moore et al, 2016; 13 Bhatt, 2017 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…The noise immission rating, a systematic questionnaire developed by Coles and Lutman, was the basis for quantifying lifetime noise exposure retrospectively in the NSH. The question of how best to determine post hoc lifetime noise exposure remains a topic of current development (e.g., Guest et al, 2018;Lutman, Davis, & Ferguson, 2008;Moore, Zobaym, Mackinnon, Whitmer, & Akeroyd, 2017).…”
Section: Commentarymentioning
confidence: 99%
“…One solution, utilized by Yeend et al. (2017) and Moore et al. (2017) , is to segment the lifespan into decades and assess noise exposure habits in each.…”
Section: Methodsmentioning
confidence: 99%
“…Three basic approaches to the quantification of sound level are employed in existing self-report measures of noise exposure: No consideration of sound level; all exposure activities are weighted equally (e.g., Liberman et al., 2016; Moore et al., 2017 ). Sound level is estimated for each exposure activity using databases of sound level measurements (e.g., Bramhall et al., 2017 ; Johnson et al., 2017 ; Yeend et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%